Pendidikan Moderasi Beragama Melalui Kajian Tafsir Ayat-Ayat Moderat di Rumah Belajar Serambi Jombang - Tri Wahyudi Ramdhan; Saifuddin Saifuddin (Dharma: Jurnal Pengabdian Masyarakat, 2023)
This service activity departs from the general theory that violence in the name of religion stems from an exclusive and intolerant understanding of religion that deserves attention and as much as possible to contain its spread. For that reason, the service aims to provide counseling and understanding of religious awareness that is moderate, inclusive, and tolerant through a study of the interpretation of moderate verses at the Serambi Jombang Learning House. This activity uses the Participatory Action Research method through a study of the interpretation of moderate verses to 60 participants. The service material given to the community related to the theme of religious moderation education service is the delivery of selected verses, especially those related to the values and principles of religious moderation. The result of this activity is that the implementation of this activity consists of three stages, each stage having the first theme of the study of non-Muslims in the Qur'an. The second is about human values in the Qur'an. The third is about religious moderation from the perspective of the Qur'an. This Community Service is expected to provide benefits and impacts including understanding the religion of the community which tends to be moderate, because the attitude of moderation in religion is very.